How they won Rugby World Cup through height, mass and collective experience - Sedeaud, A.; Marc, A.; Schipman, J.; Tafflet, M.; Hager, J.-P.; Toussaint, J.-F. (British Journal of Sports Medicine, 2012)
Objectives: To investigate the evolution of anthropometric characteristics in World Cup rugby players and identify elements associated with performance.